Application of the Poka Yoke Method in the Mix Packing Part Process to Control the Amount of Flow Out - Much Djunaidi; Nadari Octaviani Pahlevi (OPSI, 2021)
One of the activities of the Karawang ADM Engine Plant in component export is to mix part packing, which is the process of combining several component parts with a certain quantity box into one pallet. This is done to streamline delivery to the destination country. This research was conducted to analyze problems and make improvements in order to achieve the target of zero flow out with the Poké Yoke approach, to design processes or tools so that errors do not occur or at least can be detected or corrected. The flow out occurs when the clip hose part separates from the module and the part way brake actuator is left in the consumable area. Identify the problem using why analysis and the main factors that cause the flow out of man, methods, and environment factors. Some improvement ideas based on Poké Yoke ideas are presented at the end.